ABC of epilepsy - Smithson, Henry; Walker, M. C. (ABC series, 2012)
"This practical guide to the classification and diagnosis of epilepsy provides coverage of what epilepsy is, how to make the diagnosis, anti-epileptic drugs, nondrug treatments, and living with epilepsy. Richly illustrated, the book will also address epilepsy within special groups such as women, children and those with learning disabilities, as well as providing guidance on long term monitoring and review, and support and self-management. Written for GPs and related primary health care professionals, this book reflects current NICE guidelines"--Provided by publisher